ANALISIS POTENSI LIKUIFAKSI AKIBAT GEMPA BUMI BERDASARKAN DATA INSITU TEST MENGGUNAKAN METODE PROBABILITAS - Ahmad Latiful Ansori; Hanindya Kusuma Artati (Prokons: Jurnal Teknik Sipil, 2021)
Abstract The occurrence of an earthquake will cause damage to the soil structure which is called liquefaction. One of the damage to the soil structure is liquefaction. This event will affect the structure above, especially if it occurs in saturated sandy soils. The purpose of this study is to analyze the probability liquefaction based on N-SPT, and to analyze the relationship between soil and seismic parameters with the probability of liquefaction. The calculation method of liquefaction potential analysis begin by using equations suggested by the National Center for Earthquake Engineering Research (NCEER) USA based on N-SPT data to determine the liquefaction potential deterministically. Then continued with the probability calculation method proposed by Haldar & Tang (1979), Hwang et al (2004), Sonmez & Gokceoglu (2005), and Juang et al (2004). The results of the analysis show that the research location is a potential liquefaction area with a level of danger that is almost certain that it will liquefy or a probability of above 85%. The relationship of soil parameters on the probability is of N-SPT value correlated with a decrease in the probability value of liquefaction. The probability of liquefaction above 85% occurs in the N-SPT value range of 0-20, while below 85% occurs at the N-SPT value of 20-50. The increase in the value of the earthquake magnitude correlates with the high probability value of liquefaction. Keywords : Liquefaction, N-SPT data, Probability, Earthquake magnitude